Building Spiritual Intelligence within the Framework of Islamic Educational Philosophy: Reflections on the Lifestyle of Urban Communities - Winda Islamitha Nurhamidah; Mahmud Arif (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Building Spiritual Intelligence within the Framework of Islamic Educational Philosophy: Reflections on the Lifestyle of Urban CommunitiesObjective: This study examines the development of spiritual intelligence among young people through the integration of three pillars: family, school, and community, and analyzes how collaboration between these elements forms a holistic model for spiritual development among urban youth in Yogyakarta. Method: Using a descriptive qualitative approach through literature analysis, contextual observation, and conceptual review of spiritual education patterns in three main environments. Results: Effective spiritual guidance requires the internalization of religious values within the family, the strengthening of moral structures through school curricula and culture, and the expansion of spiritual experiences through socio-religious activities in the community. This integration improves adolescents' inner balance, reflective abilities, and psychological resilience in the face of urban pressures. Conclusion: This collaborative model not only produces individuals who are ritually devout but also spiritually mature and capable of making wise moral decisions. Contribution: This study provides a framework for spiritual guidance that can be applied by Islamic educational institutions, families, and local communities continuouslyINDONESIAN: Membangun Kecerdasan Spiritual dalam Bingkai Filsafat Pendidikan Islam: Refleksi atas Gaya Hidup mayarakat UrbanTujuan: Penelitian ini mengkaji pengembangan kecerdasan spiritual generasi muda melalui integrasi tiga pilar: keluarga, sekolah, dan masyarakat, serta menganalsisi bagaimana kolaborasi antarelemen tersebut membentuk model pembinaan spiritual yang holistik bagi remaja urban Yogyakarta. Metode: Menggunakan pendekatan kualitatif deskriptif melalui analisis literatur, observasi kontekstual, dan telaah konseptual terhadap pola pendidikan spiritual di tiga lingkungan utama. Hasil: Pembinaan spiritual yang efektif membutuhkan kesinambungan internalisasi nilai religius dalam keluarga, penguatan struktur moral melalui kurikulum dan budaya sekolah, serta perluasan pengalaman spiritual melalui aktivitas sosial-keagamaan di masyarakat. Integrasi ini meningkatkan keseimbangan lahir–batin, kemampuan reflektif, dan ketahanan psikologis remaja menghadapi tekanan urban. Kesimpulan: Model kolaboratif ini tidak hanya menghasilkan individu yang taat secara ritual, tetapi juga matang secara spiritual dan mampu membuat keputusan moral secara bijaksana. Kontribusi: Penelitian ini menawarkan kerangka pembinaan spiritual yang dapat diterapkan oleh lembaga pendidikan Islam, keluarga, dan komunitas lokal secara berkelanjutan.